Optimizing Compensation and Motivation in Increasing Job Satisfaction and Employee Performance - Ananda , Dalvina (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Job satisfaction and employee performance are two key aspects in the context of human resource management that affect organizational success, compensation and motivation are the two main factors that influence these two aspects. However, a deeper understanding of how compensation and motivation can affect job satisfaction and employee performance simultaneously. Through a comprehensive analysis, this study aims to identify the impact of compensation and motivation on employee job satisfaction, as well as how job satisfaction contributes to improving employee performance. This study uses quantitative survey methods involving a number of respondents from various layers in an organization. Questionnaires were used to collect data on employees' perceptions of compensation, motivation, job satisfaction, and performance. The data is then statistically analyzed using a variety of analysis techniques, including regression to identify relationships and impacts between variables. The results of this study revealed a significant relationship between compensation, motivation, job satisfaction, and employee performance. Fair compensation and high motivation have been shown to contribute positively to employee job satisfaction. In addition, high job satisfaction also has a positive impact on employee performance. These findings underscore the importance of prudent compensation management and effective motivational strategies in improving organizational performance.